A Case of Spontaneous Mediastinal and Subcutaneous Emphysema in a Patient with HIV-Infected Pneumonia - Li, Jun-Chen; Nie, Gang; Dai, Hai-Feng (Current HIV Research, 2022)
Background: Acquired immunodeficiency syndrome is a chronic infectious disease with high mortality and is caused by the Human Immunodeficiency Virus (HIV). Pneumonia caused by HIV is common, but it rarely causes spontaneous mediastinal and subcutaneous emphysema. Case Presentation: A 21-year-old man with severe pneumonia was hospitalized owing to dyspnea that had been persisting for 1 day; blood test results confirmed HIV infection. Initial chest Computed Tomography (CT) did not reveal mediastinal or subcutaneous emphysema. However, after 21 days of treatment, the patient experienced discomfort in the neck region and experienced the feeling of snowflakes on applying pressure. Chest CT showed mediastinal and subcutaneous emphysema, located in the bilateral cervical roots, anterior upper chest wall, left axillary chest wall, mediastinum, and other parts. Metagenomic Next Generation Sequencing (mNGS) of the sputum and blood samples suggested multiple pathogenic infections. Antiinfection treatment was initiated, and changes in the patient’s condition were monitored. The patient’s subcutaneous emphysema improved during the follow-up. Conclusion: In HIV-infected patients with sudden mediastinal and subcutaneous emphysema, mNGS can be used to determine the etiological agent during symptomatic treatment. Targeted antipathogen therapy is helpful in improving the condition of patients with subcutaneous emphysema.
Keywords: targeted anti-pathogen therapy